The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/rcs.2140
|View full text |Cite
|
Sign up to set email alerts
|

Capsule robot for gut microbiota sampling using shape memory alloy spring

Abstract: Background: Human gut microbiota can provide lifelong health information and even influence mood and behaviour. We currently lack the tools to obtain a microbial sample, directly from the small intestine, without contamination. Methods: Shape memory alloy springs are used in concentric configuration to develop an axial actuator. A novel design of sampling mechanism is fabricated for collecting the sample from the gut. Storage chamber (500 µl) is used to protect the sample from downstream contamination. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…It should be noted that the Bluetooth low energy protocol uses Gaussian frequency shift keying (GFSK) modulation, which plays a role in improving the receiver sensitivity of the system [30]. Real part of relative dielectric permittivity 3 Imaginary part of relative dielectric permittivity 4 Conductivity 5 Theoretical RF attenuation rate 6 Average infiltrated Table I also presents the theoretical RF attenuation rate for each medium at 2.4 GHz as derived from the relative permittivity. The real (ε′) and imaginary (ε′′) parts of the relative permittivity of a medium can be used to calculate the loss tangent [32]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the Bluetooth low energy protocol uses Gaussian frequency shift keying (GFSK) modulation, which plays a role in improving the receiver sensitivity of the system [30]. Real part of relative dielectric permittivity 3 Imaginary part of relative dielectric permittivity 4 Conductivity 5 Theoretical RF attenuation rate 6 Average infiltrated Table I also presents the theoretical RF attenuation rate for each medium at 2.4 GHz as derived from the relative permittivity. The real (ε′) and imaginary (ε′′) parts of the relative permittivity of a medium can be used to calculate the loss tangent [32]:…”
Section: Resultsmentioning
confidence: 99%
“…Wireless medical devices that can be implanted or ingested are becoming more prevalent [1][2][3][4][5][6][7][8][9][10][11][12]. Many of these devices use proprietary radio protocols operating in industrial, scientific and medical (ISM) bands such as 433 MHz and 915 MHz [13,14] or standardised radio protocols, specifically for medical use like MedRadio (formerly medical implant communication service (MICS)) and the wireless medical telemetry service (WMTS) [15].…”
Section: Introductionmentioning
confidence: 99%
“…The frictional forces are further elaborated in (2), where µ is the coefficient of friction, F s is the normal force on the sampler, F s is the force due to the deformation of the intestine, δ is the coefficient of viscosity, N v is the radial stress on the sampler and v is the velocity of sampler. These forces are elaborated in our previous work, and overall frictional forces can be considered as 200mN [35].…”
Section: B Modelling Of Intestinal Forcesmentioning
confidence: 99%
“…A wireless transmitter is used to initiate the sampling process once the robotic capsule has reached the target site. In our previous work, a sampling mechanism was developed with an active pull-out scrapping component to collect the microbiota and a chamber to store the sample [35]. The preliminary testing of the design revealed that it collected the microbiota, mucus and digesta.…”
Section: Introductionmentioning
confidence: 99%
“…Ingestible capsules are becoming more prevalent as medical devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. However, the reliability of their communications systems is still challenging.…”
Section: Introductionmentioning
confidence: 99%